Analysis of Seismic Vulnerability Index on Slope Stability in Landslide-Prone Areas of Tomilito District, North Gorontalo Regency - Demulawa, Meilan; Irsan, Irsan (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study analyzes the seismic vulnerability index to slope stability in landslide-prone areas, Tomilito District, North Gorontalo Regency. The results of the study indicate that the seismic vulnerability index in this area is in the low category, which is at a vulnerable level (0.2246-1.047736) where if vibrations occur, the surface soil layer level does not experience deformation or changes in the soil so that it is safe from the influence of shaking reinforcement.